Lifelong Learning for Personal and Professional Development in Malaysia - Ting, Su Hie; Siti Halipah, Ibrahim; Rohaida, Affandi; Azhaili, Baharun; Wan Azlan, Wan Zainal Abidin; Ui-Hang, Edmund Sim (Institute Press, 2015)
The study examined economic and non-economic benefits of non-formal lifelong learning for participants. A survey of 1,923 participants of non-formal lifelong learning programmes offered by six ministries in Malaysia showed that 50% participated in programmes that are related to the jobs and 50% participated in non job-related programmes. In the category of job-related lifelong learning programmes, participants of technical skills-based programmes are the most likely to enjoy salary increment and promotion. For others, the employment benefits are in the form of additional opportunities for training and increased job responsibilities. Besides bringing about personal development, non job-related lifelong learning programmes also endowed participants with useful skills and knowledge to earn additional income, get a job, and set up small businesses. For lifelong learning programmes to bring about better economic returns, the findings indicate that the programmes need to be structured based on skill levels (basic to advanced) and market surveys need be conducted to determine industry needs.